Principal Stages of Democratization and Priorities of Social and Economic Development of Kazakhstan - ADILZHANOV, Nurlykhan B. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
This article is dedicated to search of cause-and-effect relations in the stages of democratization of Kazakhstan. The key aspect is to define exact direction of development vector in respect to a new social and political basis for the Republic. This can help forecast future qualitative changes. Democratization in Kazakhstan was partially a result of avalanche global trend. The realias of the State should have complied with requirements of the global stage, so this was the main economic reason for reframing of values within a unified state. In this article the authors tell about background, pitfalls and solutions within establishment of a unique democratic model, build on the debris of the USSR system. The objective of this article is to find out true reasons and consequences of democratization in Kazakhstan, with detailed analysis of stages of its establishment since 1990. The material reveals influence of certain qualitative changes upon adopted social and political decisions.
Keywords: Republic of Kazakhstan; the Union of Soviet Socialist Republics; international relations; democratization; stages of development of democracy; social and political institutions; national values